NOTES ON THE MEDICAL SOUL HEALING IN THE PERSPECTIVE OF VIKTOR FRANKL - Aquino, Thiago Antonio Avellar de (2023)
The aim of the article was to clarify the conceptual and practical aspects of spiritual care from the perspective of the medical ministry according to Viktor Frankl’s thinking. The anthropological conception and the dynamics of the human spirit have been highlighted, in its aspects of self-transcendence and self-distancing. Therefore, an analysis of both the main concepts addressed in the medical anthropology of Viktor Frankl and his casuistries was carried out. In that way, it was possible to identify some spiritual needs of homo patiens, especially the aspiration to find a meaning in suffering. It concludes by pointing to the demand for a new mission in the area of health: The spiritual care, resulting in a medical pastoral.